Experience exchange event: Engendering the water, energy, food, and ecosystems (WEFE) nexus approach to sustainable development - Balcha, Yodit; Ndjiki, Julienne (Ngo Yebga); Ferraioli, Jesse; Ringler, Claudia; Aamer, Farwa; Elias, Marlene; Ntshalintshali-Motsa, Nompumelelo; Mwamyalla, Tumaini (Environmental Law Institute, 2024)
The greater the climate change impacts on food and water security, livelihoods, and the environment, the greater our need to work together across disciplines to tackle our shared challenges holistically. The water–energy–food–ecosystems (WEFE) nexus approach is a multi-disciplinary perspective to address complex resource and development challenges that underpin the Sustainable Development Goals. This approach offers a holistic and integrated framework for managing resources in the face of a pluri-dimensional crisis (climate, biodiversity, conflict, degradation etc.) which has profound impacts on water, energy, and food resources.